COMPARISON OF CTL LEARNING METHOD AND OPEN-ENDED METHOD APPLICATION IN TERMS OF LEARNING STYLES VIEWED FROM THE STUDENTS’ MATHEMATICS LEARNING ACHIEVEMENT AND INTEREST - Dafid Slamet Setiana (Universitas Mercu Buana Yogyakarta, 2016)
The purpose of this research is to describe: (1) the achievement and the interest in mathematics learning of the students taught using the CTL method and that of those taught using the Open-Ended method in the material on probability, (2) the effect of students’ mathematics learning styles on their achievement of mathematics on probability material, (3) the effect of students’ mathematics learning styles on their learning interest in mathematics on probability material, (4) the effect of teaching method and students’ mathematics learning styles on their achievement and interest in learning mathematics on the probability material. This research used a quasi-experimental research design by two experimental groups. The analysis of the data used normality and homogeneity testing, the multivariate analysis, and the post-hoc test involving the Bonferroni procedure.The results of the research are as follows: (1) In the probability material, the group of students taught by the CTL method has better achievement and mathematics learning interest than that of those who are taught using the Open-Ended learning method. (2) There is an learning style effect (auditory, visual, and kinesthetic) on their achievement of mathematics in the probability material.(3) There is an effect of learning style (auditory, visual, and kinesthetic) on their learning interest in mathematics probability material. (4) There is no effect of teaching method and students’ mathematics learning styles on their achievement and learning interest in mathematics in the probability material. Keywords: CTL, Open-Ended, learning styles, achievement, learning interest